2013
DOI: 10.1111/pcmr.12164
|View full text |Cite
|
Sign up to set email alerts
|

A melanoma immune response signature including Human Leukocyte Antigen‐E

Abstract: Paired cultures of early-passage melanoma cells and melanocytes were established from metastatic lesions and the uninvolved skin of five patients. In this stringent autologous setting, cDNA profiling was used to analyze a subset of 1477 genes selected by the Gene Ontology term 'immune response'. Human Leukocyte Antigen E (HLA-E) was ranked 19th among melanoma-overexpressed genes and was embedded in a transformation signature including its preferred peptide ligand donors HLA-A, HLA-B, HLA-C, and HLA-G. Mostly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 42 publications
0
32
0
1
Order By: Relevance
“…In patients with colorectal cancer, the overexpression of HLA‐E molecules associated with β2‐microglobulin was reported as a surrogate marker of a poor prognosis and a novel mechanism of tumor immune escape, whereas 1 study described high HLA‐E expression in long‐term survivors of cervical adenocarcinomas . Conversely, independent groups noticed that HLA‐E surface expression was observed on malignant melanoma cells, but not on healthy skin . Increased levels of sHLA‐E molecules were observed in the circulation of patients with melanoma, which introduced sHLA‐E as a potential immune‐related biomarker in cancer .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with colorectal cancer, the overexpression of HLA‐E molecules associated with β2‐microglobulin was reported as a surrogate marker of a poor prognosis and a novel mechanism of tumor immune escape, whereas 1 study described high HLA‐E expression in long‐term survivors of cervical adenocarcinomas . Conversely, independent groups noticed that HLA‐E surface expression was observed on malignant melanoma cells, but not on healthy skin . Increased levels of sHLA‐E molecules were observed in the circulation of patients with melanoma, which introduced sHLA‐E as a potential immune‐related biomarker in cancer .…”
Section: Introductionmentioning
confidence: 99%
“…30 Conversely, independent groups noticed that HLA-E surface expression was observed on malignant melanoma cells, but not on healthy skin. 31,32 Increased levels of sHLA-E molecules were observed in the circulation of patients with melanoma, which introduced sHLA-E as a potential immune-related biomarker in cancer. 31,33 Mechanistically, sHLA-E is able to induce apoptosis in T and NK cells by a Fas/Fas ligand-mediated pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The MEM mAbs were characterized by at least three groups [6,[8][9][10][11]. We found that they selectively bind unfolded HLA-E heavy chains free of β 2 m. Whereas mAb MEM-E/02 was particularly restricted to HLA-E in IEF/Western blotting, mAbs MEM-E/07 and MEM-E/08 cross-reacted to different extents with detergent-soluble HLA-A, -B, -C heavy chains, suggesting recognition of three distinct, although unmapped, nonconformational epitopes [6,12,13]. In contrast, using microbeads carrying HLA-E and HLA-A, -B, -C molecules, Ravindranath et al mapped mAbs MEM-E/02, MEM-E/07 and 3D12 to the same discontinuous, conformational, widely HLA-B/-C-cross-reactive epitope [8][9][10], and concluded that all these mAbs (particularly mAb MEM-E/08) are suitable to bind "intact HLA-β 2 m complexes."…”
mentioning
confidence: 97%
“…In our previous flow cytometry studies [6,[12][13][14], HLAhomozygous cell lines reacted with the MEM mAbs weakly and regardless of the coexpressed, and putatively cross-reactive [6], HLA-A, -B, -C alleles. Therefore, the cross-reactivity on HLA microbeads and the much weaker and restricted one detected in detergent lysates (Fig.…”
Section: Cross-reactivity Of Mabs To Hla-e Depends On Foldingmentioning
confidence: 99%
“…While the expression of HLA-A, -B and -C antigens are frequently lost or downregulated on tumor cells, HLA-G and/or HLA-E antigens are often overexpressed in tumors of distinct origin, e.g., ovarian carcinoma, colon carcinoma and melanoma. [27][28][29] Since HLA-E can bind to the inhibitory CD94/NKG2A receptors expressed on NK cells and a subset of T cells, HLA-E expression could lead to an escape of tumor cells from immune surveillance. 30 Interestingly, the selenocompound selenite is able to reduce HLA-E antigen expression in different tumor cells, which was accompanied by an enhanced NK cell-mediated killing 31 suggesting that selenite might be able to potentiate the antitumor cytotoxicity in settings of NK cell-based immunotherapies.…”
Section: Introductionmentioning
confidence: 99%